Introducing C phase in additively manufactured Ti-6Al-4V: A new oxygen-stabilized face-centred cubic solid solution with improved mechanical properties. (December 2022) - Wang, H.; Chao, Q.; Cui, X.Y.; Chen, Z.B.; Breen, A.J.; Cabral, M.; Haghdadi, N.; Huang, Q.W.; Niu, R.M.; Chen, H.S.; Lim, B.; Primig, S.; et al.
Graphical abstract: Abstract: An oxygen-rich face-centred cubic (FCC) Ti phase was engineered in the microstructure of a Ti-6Al-4V alloy via additive manufacturing using laser powder bed fusion. Designated 'C', this oxygen-rich FCC phase has a lattice parameter of 0.406 nm and exhibits an orientation relationship with the parent α′ phase as follows: (0 0 0 1)α′ //1 1 1C, and 〈 1 2 ¯ 10 〉 α ′ // 〈 1 1 ¯ 0 〉 C . We propose that the formation of the C phase is facilitated by the combined effect of thermal gradients, deformation induced by the martensitic transformation, and local O enrichment. This enables an in-situ phase transformation from the hexagonal close-packed α′ phase to the C phase at elevated temperatures. Our density functional theory calculations indicate that oxygen occupancy in the octahedral interstices of the FCC structure is energetically preferred to corresponding sites in the α′ phase. The in-situ mechanical testing results indicate that the presence of the FCC phase significantly increases the local yield strength from 1.2 GPa for samples with only the α′ phase to 1.9 GPa for samples comprising approximately equal volume fractions of the α′ and FCC phases. No loss of ductility was reported, demonstrating great potential for strengthening and work hardening. We discuss the formation mechanism of the FCC phase and a pathway for future microstructural design of titanium alloys by additive manufacturing.